Communication : 18 special works by Liverpool Academy members on the theme. - Liverpool Academy Gallery, Liverpool (Liverpool : Walker Art Gallery, 1973)
Arthur, Lawrence ; Ballard, Arthur ; Ballard, Carol ; Baum, John ; Bolger, William ; Bradford, Dorothy ; Clapham, David ; Cockrill, Maurice ; Henri, Adrian ; Murray, Margaret ; etc.
18 special works by Liverpool Academy members on the theme communication, Liverpool Academy Gallery, Liverpool, 29th Nov - 30th Dec 1973
boek